Molecular analyses and species distribution models indicate cryptic northern mountain refugia for a forest-dwelling ground beetle - Drees, C.; Husemann, M.; Homburg, K.; Brandt, P.; Dieker, P.; Habel, J.C.; Wehrden, H. von; Zumstein, P.; Assmann, T. (Wiley, 2016)
Identification of potential glacial refugia and post‐glacial colonization processes of a flightless, cold‐adapted ground beetleCentral and eastern Europe.We analysed the genetic structure of 33 Carabus sylvestris populations sampled across its entire distribution range using nuclear and mitochondrial markers. We further compiled occurrence records to develop species distribution models to predict distribution ranges for the last glacial period and the present based on the species’ current climatic niche.Distinct genetic lineages were detected for a number of mountain ranges and were congruent for both molecular marker systems. Most genetic splits were the results of vicariance, whereas dispersal was rare. Our models suggest that the species’ distribution range was larger and more interconnected in the past.Our data support multiple glacial refugia for C. sylvestris, some of which were located north of the Alps. Some lower mountain ranges were likely recolonized post‐glacially.